Viktor Shklovsky in Dialogue with Shakespeare - Mnikh, Liudmila (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2019)
The article investigates references to Shakespeare in the works of Viktor Shklovsky, an outstanding representative of the Russian formalism. The author of the paper analyses literary studies by Shklovsky in which Shakespeare’s texts are interpreted. In his early works (dating to the 1920s–1930s) Shklovsky referred to Shakespeare to justify the new terminology of the Russian formalism, while his later works were devoted to the study of Shakespeare’s texts.